2009
DOI: 10.1007/s12192-008-0070-0
|View full text |Cite
|
Sign up to set email alerts
|

Caloric stress alters fat characteristics and Hsp70 expression in milk somatic cells of lactating beef cows

Abstract: Selection for higher production rate in cattle inhabiting challenging habitats may be considered disadvantageous because of possible deleterious effects on immunity and reproduction and, consequently, on calf crop percentage. In Israel, free-grazing high productive beef cows experience reduction in nutritional quality of forage during up to 8 months of the year. As milk production by dams dictates calf performance, dam's nutritional needs and rebreeding rates, the aim of the present study was to test how lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 39 publications
4
12
0
Order By: Relevance
“…Likewise, Yániz et al (2009) reported that conditions of mild hot did not affect Hsp72 concentrations in PBMC from early or mid-pregnant cows. Finally, no effect of summer heat stress was reported in the expression of Hsp70 in lymphocytes isolated from beef cattle (Eitam et al 2009) or dairy cows (do Amaral et al 2010). Therefore, values of summer THI recorded during the present study are likely to justify the lack of significant differences between SP and SU cows for the parameters under investigation.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Likewise, Yániz et al (2009) reported that conditions of mild hot did not affect Hsp72 concentrations in PBMC from early or mid-pregnant cows. Finally, no effect of summer heat stress was reported in the expression of Hsp70 in lymphocytes isolated from beef cattle (Eitam et al 2009) or dairy cows (do Amaral et al 2010). Therefore, values of summer THI recorded during the present study are likely to justify the lack of significant differences between SP and SU cows for the parameters under investigation.…”
Section: Discussionmentioning
confidence: 60%
“…Some studies demonstrated that caloric restriction, hypoglycaemia, or hyperlipidemia may differentially regulate Hsp expression in different body compartments. Eitam et al (2009) reported that a prolonged low-energy diet promoted cell-specific Hsp response in bovine with a significant increase of Hsp90 but unchanged levels of Hsp70 mRNA in white blood cells, and a lower expression of Hsp70 in milk somatic cells. Interestingly, Febbraio et al (2004) demonstrated that maintaining glucose availability during exercise attenuates the circulating Hsp72 response in healthy humans.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summaries some of the most important signaling molecules involved in CR-induced biological and physiological responses. FOXO ↓ [89,97] GSK-3β ↓ [93,98] HIF-1 ↓ [95,99] HSF-1 ↑ [94] HSP-70 ↑ [94,100] mTOR ↓ [90,101] NF-κB ↓ [81,82,95,97] PGC-1α ↑ [91,92] PPAR α ↑ [91,102] SIRT1 ↑↓ [92,93,103] ↑=increase in signal transduction; ↓=decrease in signal transduction.…”
Section: Signal Transduction Mechanism Involved In Crmentioning
confidence: 99%
“…Theoretically, the high frequency of GG genotype observed in BAL and Israeli SIM may partially be related to their adaptation to poor nutritional conditions, likely to occur in the Southern Mediterranean basin. Indeed, when lactating SIM cows were exposed to low energy and protein diet, they switched their milk fatty acids in favor of mono-and polyunsaturated ones [42].…”
Section: Discussionmentioning
confidence: 99%